Preservative Premix With Fumaric Acid for Use in the Bakery Industry (2023)
Innovative healthy solutions as alternatives to food preservatives to prevent food waste is of interest to food companies since microorganisms are increasingly resistant to current alternatives. For this purpose, the antimicrobial effect of fumaric acid (FA) with preservatives and organic acids on food spoilage molds and evaluate their efficiency and possible synergy in vitro and applied in Muffins. Calcium propionate (CP), potassium sorbate (PS), citric acid (CA), lactic acid (LA) were used to evaluate their inhibitory capacity alone and in mixtures with (FA) on three species of molds, measuring the growth radius in Petri dishes and calculating inhibition percentages (% I). When the best mixture was selected, it was added to muffins, that were evaluated for 17 days by counting molds and yeasts. The highest % I was for Penicillium sp. 89 % with SP. For A. flavus 54 % with AC and AL and for A. niger 70 % I with LA. The highest variability in antimicrobial effects was for Penicillium sp. The selected mixture was AF 2000 ppm with SP 300 ppm. When applied to muffins, the effect on storage time could not be established, although it presented less diversity of isolated colonies. The % I was different for each preservative and mold species at the concentrations evaluated, and the antimicrobial effect of FA alone and in mixture with potassium sorbate for the control of different mold species was evident.